A new molecular mechanism of RNA circularization and the microRNA sponge formation. Issue 7 (3rd May 2022) - Belter, Agnieszka; Popenda, Mariusz; Sajek, Marcin; Woźniak, Tomasz; Naskręt-Barciszewska, Mirosława Z.; Szachniuk, Marta; Jurga, Stefan; Barciszewski, Jan
Abstract: A new mechanism of RNA circularization driven by specific binding of miRNAs is described. We identified the 71 CUUCC pentanucleotide motifs distributed regularly throughout the entire molecule of CDR1as RNA that bind to 71 miRNAs through their seed sequence GGAAG. The sequential binding of miR-7 RNAs (71 molecules) brings both ends of CDR1as RNA (1 molecule) together and stimulate phosphodiester bond formation between nucleotides C1 and A1299 at the 5' and 3' end, respectively. The binding of miRNAs to CDR1as RNA results in the unique complex formation, which shows three specific structural domains: (i) two short helixes with an internal loop, (ii) the hinge, and (iii) the triple-helix. The proposed mechanism explains specific RNA circularization and its function as a miRNAs sponge. Furthermore, the existing wet experimental data on the interaction of CDR1as RNA with miR-7 fully supports our observation. Although miR-671 shows the same seed sequence as miR-7, it forms an almost perfect double helix with CDR1as RNA and induces the cleavage of CDR1as, but does not stimulate circularization. To check how common is the proposed mechanism among circular RNAs, we analyzed the most recent circAtlas database counting almost 1.1 million sequences. It turned out that there are a huge number of circRNAs, which showed miRNAs seed binding sequences distributed through the whole circRNA sequences and prove that circularization of linear transcript is miRNA dependent. Communicated by Ramaswamy H. Sarma